The Dynamics of Educational Marketing: An Islamic Boarding School's Strategy Following a Sexual Harassment Case in Tangerang - Ahmad Bustomi; Isti Fatonah; Zulihi Zulihi (IAIN Manado, 2026)
The purpose of this research is to describe the marketing strategies of an Islamic boarding school in Tangerang to restore its image and increase prospective students' interest following a sexual harassment case. This study employed a field research approach. Data were collected through interviews, documentation, and observation. The data sources were the kiai (head of the Islamic boarding school), asatidz (religious teachers), and the students' parents or guardians. The results of this research show that the Islamic boarding school used four marketing strategies to restore its image and increase prospective students' interest following the sexual harassment case, including strategic planning, social media use, improvements in teacher quality, activity monitoring, and facility upgrades.